(Mis)communicating climate change? Why online adaptation databases may fail to catalyze adaptation action - Mitchell, Carrie L.; Burch, Sarah L.; Driscoll, Patrick A. (Wiley Interdisciplinary Reviews: Climate Change, 2016)
Over the last decade a plethora of action-oriented research projects h as been conducted in developing countries, exploring how to effectivel y adapt to the anticipated impacts of climate change. Many intergovern mental agencies and development organizations have chosen to dissemina te their research results via online databases. It is unclear, however , whether these databases are useful in terms of actual adaptation pla nning and implementation. A systematic review of online databases has found at least 64 databases and tools online related to climate change adaptation. Despite the abundance of databases, this analysis reveals that the existing body of online databases generally lack the structu re and mechanics to identify, extract, and synthesize both effective a nd ineffective climate change adaptation practices, projects, programs , and policies. Even relatively basic information, such as identificat ion of projects’ projected versus actual costs is absent, which are cr ucial decision-making criteria particularly in developing country cont exts where resource constraints are significant. In this paper we eval uate these online tools with a focus on identifying features that pote ntially could contribute to knowledge sharing and successful exchange of climate change adaptation projects and practices within a developin g country context. We conclude the paper with recommendations for how to improve efforts to communicate climate change research, such as mor e nuanced needs assessments of potential users of databases. WIREs Cli m Change 2016, 7:600–613. doi: 10.1002/wcc.401 This article is categor ized under: Vulnerability and Adaptation to Climate Change > Instituti ons for Adaptation Climate and Development > Knowledge and Action in D evelopment Social Status of Climate Change Knowledge > Knowledge and P ractice